Forestry management and water law: comparing Ecuador and Arizona. Issue 3 (3rd April 2019) - Martínez Moscoso, Andrés; Larson, Rhett
ABSTRACT: This article compares public–private partnerships dedicated to improving forestry management to protect water in the Paute River basin in Ecuador (FONAPA) and the Verde River basin in Arizona (the Four Forest Restoration Initiative). Both programmes create incentives for improved forestry management and suggest lessons for water management in general but may face legal challenges that require reforms. While there is scope for mutual learning between the programmes, such cross-fertilization is inhibited by differences in the legal status of water and forest resources in the two systems.